Pengenalan dan Penerapan Biopori Sebagai Lubang Resapan di SMPN 2 Dringu Kabupaten Probolinggo - Dewi, Indah Noor Dwi Kusuma; Muhammad, Alief; Baihaqi, Mas Ahmad; Hermawan, Nanang; Triyastutik, Annisa Ayu; Dini, Joko Sugiono Eka Prasetya; Putri, Salsabillah Widya Eka; Kurniawan, Tri Nanda Indra; Nisak, Indani Khoirun; Setyawati, Ika (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The community service activity at SMPN 2 Dringu in Probolinggo Regency aimed to address environmental issues within the school, specifically the frequent waterlogging in certain areas that disrupted activities and posed safety risks. As a solution, the introduction and implementation of Biopore Infiltration Holes (LRB) were carried out at the school. Biopores function to enhance water infiltration, reduce waterlogging, and improve soil quality. This community service activity involved observation, preparation, as well as conducting educational sessions and practical biopore planting by students, with the goal of raising awareness and enhancing capabilities in addressing environmental issues. The results of the activity showed a reduction in waterlogging duration by up to three hours and a decrease in organic waste volume through the use of biopores as compost. The implementation of biopores not only helped mitigate flood risks but also improved the school's environmental quality, supporting sustainability and environmental health.